Dry-method binder as well as preparation method and application thereof
By setting an elastic polymer layer on the surface of the fibrotic bondable material, the problem of side reaction of dry adhesive in the battery is solved, the cycle stability and Coulomb efficiency of the battery are improved, and the structural stability and electrochemical performance of the electrode are improved.
Patent Information
- Application Number
- CN202510702070.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2025-08-22
AI Technical Summary
The existing dry adhesives are prone to side reactions in batteries, resulting in reduced battery capacity and poor cycle stability, especially at low negative potential.
An elastic polymer layer is provided on the surface of the fibrotic bonding material, and a cladding layer is formed by polymerizing monomers under heat treatment or ultraviolet irradiation to isolate the contact between the matrix material and the active lithium and conductive agent to form a stable adhesive network.
The structural stability and electrochemical performance of the dry electrode are improved, the cycle stability and Coulomb efficiency of the battery are improved, and the structural stability and electrochemical performance of the electrode are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery technology, and in particular to a dry binder and a preparation method and application thereof. Background Art
[0002] Electrochemical energy storage devices offer the advantages of long life, low pollution, and environmental friendliness, and are currently experiencing explosive growth in areas such as electric vehicles and energy storage devices. Electrode sheets in existing energy storage devices are typically prepared using a wet process. During this process, active materials, conductive agents, and adhesives are dispersed in a large amount of deionized water and N-methylpyrrolidone to form a slurry. This slurry is then coated on a current collector and dried to produce the electrode sheet. However, N-methylpyrrolidone is toxic, posing a health risk to operators and the environment during the coating process. Furthermore, the drying process consumes significant energy, making it difficult to meet the increasingly prominent energy conservation and environmental requirements.
[0003] The dry electrode is a solvent-free manufacturing process. No solvent is used in the entire stirring and coating process during the preparation process, so there is no need for drying, which greatly reduces energy consumption. It is also suitable for the manufacture of thick electrodes, reducing the floating of binders during the drying process, and can improve the performance consistency of lithium-ion batteries. Therefore, the development of dry electrodes can effectively meet the requirements of environmental friendliness and energy saving and consumption reduction. The commonly used binder for existing dry electrodes is polytetrafluoroethylene (PTFE), but commercial PTFE powder is prone to agglomeration during the preparation of dry electrodes and is difficult to disperse evenly. At the same time, excessive addition to the electrode will lead to excessive battery polarization and serious battery cycle attenuation. The most important thing is that PTFE has side reactions at low points in the negative electrode, which consumes active lithium in the battery and reduces the battery's capacity and cycle stability.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] One object of the present invention is to provide a dry binder to solve the technical problem that conventional dry binders are prone to side reactions, thereby reducing the capacity and cycle stability of batteries.
[0006] Another object of the present invention is to provide a method for preparing a dry binder, which is simple and easy to implement. The obtained dry binder is stable at low potential and can improve the electrochemical performance of the electrode.
[0007] Another object of the present invention is to provide a dry-process negative electrode film layer.
[0008] Another object of the present invention is to provide a dry-process negative electrode.
[0009] Another object of the present invention is to provide a battery.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted: A dry adhesive comprises a base material and an elastic polymer layer disposed on the surface of the base material; the base material comprises a fiberizable adhesive material; the elastic polymer layer is formed by polymerizing monomers, wherein the polymerizing monomers comprise at least one of tetrahydro-2H-2-pyrone, trimesoyl chloride, trimethylene carbonate, and trifluoropropylene.
[0011] In some embodiments, the fiberizable bonding material includes polytetrafluoroethylene and / or a copolymer containing polytetrafluoroethylene.
[0012] In some embodiments, the tetrafluoroethylene-containing copolymer includes at least one of ethylene-tetrafluoroethylene copolymer, polyperfluoroethylene propylene, tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer, and ethylene-chlorotrifluoroethylene copolymer.
[0013] In some embodiments, the mass of the elastic polymer layer is 2% to 10% of the mass of the dry binder.
[0014] In some embodiments, the elastic polymer layer has a thickness of 2-10 nm.
[0015] A method for preparing a dry adhesive comprises the following steps: The polymerization monomer, the initiator and the pre-treated fiberizable adhesive material are mixed to obtain a first system; and heat treatment and / or ultraviolet irradiation treatment are performed to obtain a dry adhesive.
[0016] In some embodiments, the fiberizable bonding material includes at least one of polytetrafluoroethylene and a copolymer containing tetrafluoroethylene. The copolymer containing tetrafluoroethylene includes at least one of ethylene-tetrafluoroethylene copolymer, polyperfluoroethylene propylene, tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer, and ethylene-chlorotrifluoroethylene copolymer.
[0017] In some embodiments, the polymerizable monomers include one or more of tetrahydro-2H-2-pyrone, trimesoyl chloride, trimesoyl carbonate, and trifluoropropylene.
[0018] In some embodiments, the mass ratio of the fibrillable adhesive material to the polymerizable monomer is (0.1-10):1, preferably (0.1-0.4):1.
[0019] In some embodiments, the initiator includes azobisisobutyronitrile.
[0020] In some embodiments, the mass ratio of the initiator to the polymerization monomer is (0.1-5): (80-100).
[0021] In some embodiments, the pretreatment includes: ultrasonic treatment, washing treatment and drying treatment; the ultrasonic treatment frequency is 100kHz~1000kHz, the ultrasonic treatment time is 5~20min, and the ultrasonic treatment temperature is 25~50°C.
[0022] In some embodiments, the mixing process is performed under protective gas conditions.
[0023] In some embodiments, the rotation speed of the mixing process is 50-500 r / min, and the mixing time is 10-40 min.
[0024] In some embodiments, the heat treatment temperature is 30-120° C., preferably 40-60° C., and the heat treatment time is 1-5 hours.
[0025] In some embodiments, the heat treatment uses a constant temperature water bath and / or a constant temperature oil bath.
[0026] In some embodiments, the material obtained after the heat treatment is cooled and washed to obtain the dry binder.
[0027] A dry-process negative electrode film layer is prepared from raw materials including a dry-process binder, an electrode active material and a conductive agent; the dry-process binder is the dry-process binder described above or a dry-process binder prepared by the preparation method of the dry-process binder described above.
[0028] In some embodiments, the dry-process negative electrode film layer includes a dry-process negative electrode film layer.
[0029] In some embodiments, the preparation method of the dry-process negative electrode film layer specifically includes: performing low-temperature mixing treatment on the mixture of the dry-process binder, the electrode active material and the conductive agent, the temperature of the low-temperature mixing treatment is 3~10°C, and the dispersion disk linear speed of the low-temperature mixing treatment is 5~25m / s; then performing high-temperature mixing treatment, the temperature of the high-temperature mixing treatment is 130~150°C, and the rotation speed of the high-temperature mixing treatment is 35~45m / s to obtain the electrode material; and performing film-forming treatment on the electrode material to obtain a dry-process negative electrode film layer.
[0030] A dry-process negative electrode comprises an electrode current collector, a conductive adhesive layer and the dry-process negative electrode film layer; the conductive adhesive layer is located on at least one side surface of the electrode current collector; the dry-process negative electrode film layer is located on the surface of the conductive adhesive layer away from the electrode current collector.
[0031] A battery comprises the dry-process negative electrode.
[0032] Compared with the prior art, the present invention has the following beneficial effects: (1) The dry binder of the present invention is provided with an elastic polymer layer on the surface of the fibrillable binder material. The elastic polymer layer has a certain degree of deformability. During the fibrillation process of the fibrillable binder, the coating layer can still form a package. The coated elastic polymer layer is stable at low potential and will not react with the components in the battery. It can isolate the base material from the contact with the active lithium and the conductive agent. By coating the elastic polymer layer, the problem of the side reaction of the binder on the negative electrode side in the dry electrode is solved, thereby making the structure of the dry electrode more stable and improving the cycle stability and coulombic efficiency of the battery.
[0033] (2) The preparation method of the dry binder of the present invention is simple and easy. The fiberizable binder, a polymerizable monomer and an initiator are mixed to fully disperse the fiberizable binder. The fiberizable binder is then subjected to heat treatment and / or ultraviolet irradiation treatment to cause the polymerizable monomer to undergo a polymerization reaction on the surface of the fiberizable binder, forming an elastic polymer layer that coats the surface of the fiberizable binder, thereby obtaining a dry binder. The dry binder obtained by the method of the present invention has excellent physical and chemical properties and can be cross-linked to form a binder network. The coating layer can isolate electron conduction in the electrode structure, effectively inhibit the side reactions of the fiberizable binder, improve its application effect in dry electrodes, and improve the structural stability and electrochemical performance of the electrode.
[0034] (3) The dry-process negative electrode film obtained by the dry-process binder of the present invention has excellent structural stability, so that the obtained dry-process negative electrode has good structural stability and excellent electrochemical performance, which can further improve the cycle stability and coulombic efficiency of the battery. DETAILED DESCRIPTION
[0035] The embodiments of the present invention will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present invention and should not be construed as limiting the scope of the invention. Where specific conditions are not specified in the examples, the methods were performed according to conventional conditions or the conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments are not specified, they are all commercially available conventional products.
[0036] According to one aspect of the present invention, the present invention relates to a dry adhesive, comprising a base material and an elastic polymer layer arranged on the surface of the base material; the base material comprises a fiberizable adhesive material; the elastic polymer layer is formed by polymerization of polymerized monomers, and the polymerized monomers include at least one of tetrahydro-2H-2-pyrone, trimesoyl chloride, trimethylene carbonate and trifluoropropylene.
[0037] The dry binder of the present invention is provided with an elastic polymer layer on the surface of a fibrillable binder material. The elastic polymer layer has a certain deformability. During the fibrillation process of the fibrillable binder, the coating layer can still form a wrapping. The coated elastic polymer layer is stable at low potential and will not react with the components in the battery. It can isolate the contact between the matrix material and the active lithium and the conductive agent. By coating the elastic polymer layer, the problem of the side reaction of the binder on the negative electrode side in the dry electrode is solved, thereby making the structure of the dry electrode more stable, and improving the cycle stability and coulombic efficiency of the battery.
[0038] In some embodiments, the fiberizable adhesive material comprises polytetrafluoroethylene and / or a copolymer containing tetrafluoroethylene. In some embodiments, the copolymer containing tetrafluoroethylene comprises at least one of ethylene-tetrafluoroethylene copolymer (ETFE), polyfluoroethylene-propylene copolymer (FEP), tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer (EPE), and ethylene-chlorotrifluoroethylene copolymer (ECTFE). The fiberizable adhesive material of the present invention may be a combination of one or more of the aforementioned materials, such as a combination of ETFE and FEP, or a combination of EPE and ECTFE.
[0039] In some embodiments, the mass of the elastic polymer layer is 2% to 10% of the mass of the dry binder, for example, 2%, 4%, 5%, 8%, 10%, or any range therebetween. In some embodiments, the thickness of the elastic polymer layer is 2 to 10 nm, for example, 2 nm, 3 nm, 5 nm, 8 nm, 10 nm, or any range therebetween. The elastic polymer layer of the present invention has an appropriate mass content and thickness, thereby ensuring the physical and chemical properties of the dry binder and improving the structural stability of the dry electrode.
[0040] According to another aspect of the present invention, the present invention also relates to a method for preparing a dry binder, comprising the following steps: The polymerizable monomer, the initiator and the pre-treated fiberizable adhesive material are mixed to obtain a first system. The first system is subjected to heat treatment and / or ultraviolet irradiation treatment to obtain a dry adhesive.
[0041] The preparation method of the dry binder of the present invention is simple and easy. The fiberizable binder material, a polymerizable monomer, and an initiator are mixed to fully disperse the fiberizable binder material. The fiberizable binder material is then subjected to heat treatment and / or ultraviolet irradiation treatment to cause the polymerizable monomer to undergo a polymerization reaction on the surface of the fiberizable binder material, forming an elastic polymer layer that coats the surface of the fiberizable binder material, thereby obtaining the dry binder. The dry binder obtained by the method of the present invention has excellent physical and chemical properties, can be cross-linked to form a binder network, and the coating layer can isolate electron conduction in the electrode structure, effectively suppressing side reactions of the fiberizable binder, improving its application effect in dry electrodes, and improving the structural stability and electrochemical performance of the electrode.
[0042] In some embodiments, the fiberizable binder material includes at least one of polytetrafluoroethylene and a copolymer containing tetrafluoroethylene. In some embodiments, the copolymer containing tetrafluoroethylene includes at least one of ethylene-tetrafluoroethylene copolymer (ETFE), polyfluoroethylene-propylene (FEP), tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer (EPE), and ethylene-chlorotrifluoroethylene copolymer (ECTFE). Examples include a combination of ETFE and FEP, or a combination of EPE and ECTFE.
[0043] In some embodiments, the polymerizable monomer includes one or more of tetrahydro-2H-2-pyrone, trimesoyl chloride, trimethylene carbonate and trifluoropropylene, such as a combination of tetrahydro-2H-2-pyrone and trimesoyl chloride, a combination of trimesoyl chloride and trifluoropropylene, a combination of trimesoyl chloride, trimethylene carbonate and trifluoropropylene, and the like.
[0044] In some embodiments, the mass ratio of the fibrillizable binder material to the polymerizable monomer is (0.1-10):1, for example, 0.1:1, 0.2:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc. Preferably, it is (0.1-0.4):1. The suitable mass ratio of the fibrillizable binder material to the polymerizable monomer of the present invention ensures that the elastic polymer layer on the surface of the resulting dry-process binder has an appropriate mass content and thickness, thereby ensuring the comprehensive physical and chemical properties of the dry-process binder, improving its effectiveness in the dry-process electrode, and enhancing the electrochemical performance of the dry-process electrode.
[0045] In some embodiments, the initiator comprises azobisisobutyronitrile. In some embodiments, the mass ratio of the initiator to the polymerizable monomer is (0.1-5):(80-100), for example, 0.1:80, 1:85, 2:90, 5:100, etc. The present invention utilizes an appropriate amount of initiator to ensure polymerization efficiency and the overall performance of the adhesive.
[0046] In some embodiments, the pretreatment includes ultrasonic treatment, washing, and drying. The ultrasonic treatment frequency is 100 kHz to 1000 kHz, for example, 100 kHz, 200 kHz, 500 kHz, or 1000 kHz. The ultrasonic treatment duration is 5 to 20 minutes (for example, 5 minutes, 10 minutes, 15 minutes, 18 minutes, or 20 minutes), and the ultrasonic treatment temperature is 25 to 50°C (for example, 25°C, 40°C, or 50°C). The high molecular weight fiberizable binder is ultrasonically dispersed in deionized water to remove surface impurities and aggregates. This breaks up secondary ion aggregates in the fiberizable binder to facilitate more comprehensive coating in subsequent steps. The mixture is then centrifuged, washed, and the precipitate collected and dried in an oven to a constant weight.
[0047] In some embodiments, the mixing process is performed under protective gas conditions, such as nitrogen, argon, etc. Specifically, the protective gas is introduced to remove oxygen for 3 to 7 minutes.
[0048] In some embodiments, the rotation speed of the mixing process is 50 to 500 r / min, such as 50 r / min, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, etc., or any range therebetween. The mixing time is 10 to 40 min, such as 10 min, 15 min, 20 min, 25 min, 30 min, 35 min or 40 min, etc., or any range therebetween. The present invention ensures that the materials are fully mixed by adopting appropriate mixing conditions to ensure the subsequent coating effect.
[0049] In some embodiments, the temperature of the heat treatment is 30 to 120° C., preferably 40 to 60° C., for example, 30° C., 40° C., 60° C., 80° C., 100° C., 120° C., etc., or any range therebetween. The time of the heat treatment is 1 to 5 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours or 5 hours, etc. In some embodiments, the heat treatment adopts a constant temperature water bath and / or a constant temperature oil bath. The present invention adopts appropriate heat treatment conditions to further ensure the polymerization effect of the polymerized monomers and form a suitable polymer coating layer on the surface of the fiberizable adhesive material.
[0050] In some embodiments, the material obtained after the heat treatment is cooled and washed to obtain the dry binder. The cooling process is performed to room temperature. The washing process includes repeatedly washing with a solvent to remove unadsorbed polymer until no polymer is detected in the washing liquid (the polymer concentration in the washing liquid can be monitored using an appropriate detection method, such as ultraviolet-visible spectroscopy).
[0051] In a preferred embodiment, a method for preparing a dry binder comprises the following steps: (a) Pretreating the fiberizable adhesive material, including ultrasonic treatment, washing, and drying; the ultrasonic treatment frequency is 100 kHz to 1000 kHz, the ultrasonic treatment time is 5 to 20 minutes, and the ultrasonic treatment temperature is 25 to 50°C. The pretreated fiberizable adhesive material is mixed with a polymerizable monomer and an initiator; the fiberizable adhesive (0.1 to 5): (80 to 100); the mixing is carried out under protective gas conditions, the mixing speed is 50 to 500 rpm, and the mixing time is 10 to 40 minutes, to obtain a first system.
[0052] (b) placing the first system in a constant temperature water bath and / or oil bath for heat treatment at a temperature of 30 to 120° C. for a time of 1 to 5 hours. After the reaction is completed, cooling to room temperature is performed, centrifuging the cooled mixed system, and repeatedly washing the precipitate with a solvent to remove unadsorbed polymer until no polymer is detected in the washing liquid, thereby obtaining a dry binder.
[0053] According to another aspect of the present invention, a dry-process negative electrode film is prepared from raw materials including a dry-process binder, an electrode active material, and a conductive agent; the dry-process binder is prepared using the aforementioned dry-process binder preparation method. The dry-process binder of the present invention can improve the structural stability of the dry-process negative electrode film.
[0054] In some embodiments, the dry-process negative electrode film layer includes a dry-process negative electrode film layer prepared from a dry-process binder, a negative electrode active material (graphite and / or silicon-based material), and a negative electrode conductor (at least one of conductive carbon black, carbon nanotubes, and carbon fibers).
[0055] In some embodiments, the preparation method of the dry-process negative electrode film layer specifically includes: performing low-temperature mixing treatment on the mixture of the dry-process binder, the electrode active material and the conductive agent, the temperature of the low-temperature mixing treatment is 3~10°C, and the linear speed of the dispersion disk is 5~25m / s; then performing high-temperature mixing treatment, the temperature of the high-temperature mixing treatment is 130~150°C, and the rotation speed is 35~45m / s to obtain the electrode material; and performing film-forming treatment on the electrode material to obtain a dry-process negative electrode film layer.
[0056] According to another aspect of the present invention, a dry-process anode comprises an electrode current collector, a conductive adhesive layer, and the dry-process anode film layer; the conductive adhesive layer is located on at least one side of the electrode current collector; and the dry-process anode film layer is located on the surface of the conductive adhesive layer away from the electrode current collector. The dry-process electrode of the present invention has excellent cycling stability and high coulombic efficiency.
[0057] In some embodiments, the dry-process negative electrode has a cohesive force greater than or equal to 27 N / m, for example, 27 to 60 N / m. In some embodiments, the dry-process negative electrode has a tensile strength of 0.72 to 1.2 MPa. The dry-process negative electrode of the present invention has excellent cohesive force and tensile strength.
[0058] According to another aspect of the present invention, the present invention also relates to a battery comprising the dry-process negative electrode. The battery of the present invention has excellent cycle performance and safety performance.
[0059] In some embodiments, the first efficiency of the battery of the present invention is greater than or equal to 79.5%, for example, 79.5% to 88.5%. In some embodiments, the capacity retention rate of the battery of the present invention after 2000 cycles at 25°C is greater than or equal to 73.9%, for example, 73.9% to 92.5%. In some embodiments, the capacity retention rate of the battery of the present invention after 2000 cycles at 50°C is greater than or equal to 85.7%, for example, 85.7% to 94%. The battery prepared with the dry binder of the present invention has a high first efficiency, excellent capacity retention at high temperatures, and better high-temperature cycling performance.
[0060] In some embodiments, the battery further comprises a dry-process positive electrode sheet, and the specific preparation method comprises: Positive electrode formulation: LFP:SPPTFE = 96.5%:2%:1.5%. ① Dry material mixing: Lithium iron phosphate, conductive agent, and other powders are mechanically mixed to form a uniform dry powder mixture. ② Binder fibrillation and mixing: The binder is processed into a fibrous structure, making it easier to bond with other ingredients during the dry mixing process. This step, sometimes also called fibrillation, enables the binder to exhibit a liquid-like adhesive effect in a dry state, thereby enhancing the adhesion and mechanical strength of the mixture. ③ Granulation: The fibrillated mixture is granulated using a mechanical granulation machine. After granulation, the granules have good flowability and handling characteristics, making them suitable for subsequent film formation. The granules require controlled particle size, consistent density and shape, and sufficient mechanical strength. ④ Support film formation, thinning and compaction: The granulated material is passed through a multi-roller machine. After the first roll press, the support film is formed. The second and third roll presses are used for thinning and compaction (reducing thickness, increasing density, and enhancing electrode performance), forming a stable electrode film. The electrode film thickness ranges from tens to hundreds of microns. ⑤ Electrode-current collector bonding: This is the process of firmly bonding the dry electrode film to the current collector, ensuring a strong adhesion between the dry electrode film and the current collector to provide a good electronic conductive path and mechanical stability. The electrode film and current collector are bonded using hot pressing or roller pressing equipment, and the current collector may require surface treatment to enhance adhesion.
[0061] In some embodiments, the battery further comprises a separator comprising polyethylene and / or polypropylene.
[0062] In some embodiments, the preparation of the battery specifically includes: Electrode Processing: The dry-process positive and negative electrodes are cut to the designed dimensions to ensure dimensional accuracy and edge quality, avoiding burrs and dimensional deviations that could affect battery performance. Tabs are welded to the electrode sheets. The material and weld quality of the tabs are directly related to the battery's charge-discharge performance and safety. High-precision welding processes such as laser welding are required to ensure a secure connection between the tabs and the electrode sheets with low resistance. Diaphragm Preparation: Based on the battery design requirements, the appropriate diaphragm material is selected and installed on the diaphragm unwinding mechanism of the stacking machine. Diaphragm tension control and deviation correction are performed to ensure stable tension and correct positioning during the stacking process, preventing wrinkles or deviation that could affect the stability of the battery's internal structure. Lamination Operation: The processed positive electrode sheet is placed on the stacking machine's worktable as the starting layer. The stacking machine's robotic arm or conveyor mechanism applies the diaphragm to the positive electrode sheet according to the specified path and tension, ensuring complete coverage and neat edges. Place the negative electrode sheet on the diaphragm and align it with the positive electrode sheet to ensure that the relative position between the positive and negative electrodes is accurate. Repeat the above steps, continue to stack the diaphragm and the positive and negative electrodes, and stack them according to the designed number of layers and order to form the basic structure of the battery core. Battery core shaping: After the lamination is completed, the battery core is shaped by applying a certain pressure and temperature to make the external dimensions of the battery core meet the design requirements. At the same time, the internal stress that may be generated during the lamination process is eliminated to improve the stability and consistency of the battery core. Tab welding and lead-out: Lead out the tabs of the battery core and weld them to the external connection terminals. The welding process requires strict control of welding parameters to ensure welding quality, prevent problems such as cold welding and leaking welding, and ensure good connection between the battery and the external circuit.
[0063] The following is further explained with reference to specific embodiments and comparative examples.
[0064] Example 1 A method for preparing a dry adhesive comprises the following steps: (a) The fiberizable adhesive material is pretreated, comprising ultrasonic treatment, washing, and drying; the ultrasonic treatment frequency is 480 kHz, the ultrasonic treatment time is 10 min, and the ultrasonic treatment temperature is 35°C. The pretreated fiberizable adhesive material is mixed with a polymerizable monomer and an initiator, wherein the fiberizable adhesive material is polytetrafluoroethylene; the polymerizable monomers are tetrahydro-2H-2-pyrone and trifluoropropylene (mass ratio of 2:1); the mass ratio of the fiberizable adhesive material to the polymerizable monomer is 4:1; the initiator is azobisisobutyronitrile, and the mass ratio of the initiator to the polymerizable monomer is 1:100; the mixing is carried out under nitrogen; the mixing speed is 300 r / min, and the mixing time is 30 min, thereby obtaining a first system.
[0065] (b) The first system is placed in a constant temperature water bath for heat treatment at a temperature of 55° C. for 1.5 h. After the reaction is completed, the system is cooled to room temperature. The cooled mixed system is centrifuged and the precipitate is repeatedly washed with a solvent to remove unadsorbed polymer until no polymer is detected in the washing liquid, thereby obtaining a dry binder.
[0066] Example 2 A method for preparing a dry adhesive comprises the following steps: (a) The fiberizable adhesive material is pretreated, comprising ultrasonic treatment, washing, and drying. The ultrasonic treatment frequency is 480 kHz, the ultrasonic treatment time is 10 min, and the ultrasonic treatment temperature is 35°C. The pretreated fiberizable adhesive material is mixed with a polymerizable monomer and an initiator. The fiberizable adhesive material is polytetrafluoroethylene; the polymerizable monomers are tetrahydro-2H-2-pyrone, trifluoropropylene, and trimethylene carbonate (mass ratio of 3:1:1); the mass ratio of the fiberizable adhesive material to the polymerizable monomer is 3:1; the initiator is azobisisobutyronitrile, and the mass ratio of the initiator to the polymerizable monomer is 1:100. The mixing is carried out under nitrogen at a mixing speed of 300 r / min and a mixing time of 25 min. Thus, a first system is obtained.
[0067] (b) The first system is placed in a constant temperature water bath for heat treatment at a temperature of 55° C. for 2.5 hours. After the reaction is completed, the system is cooled to room temperature. The cooled mixed system is centrifuged and the precipitate is repeatedly washed with a solvent to remove unadsorbed polymer until no polymer is detected in the washing liquid, thereby obtaining a dry binder.
[0068] Example 3 A method for preparing a dry binder differs from Example 1 in that: The mass ratio of the fiberizable bonding material to the polymerizable monomer is 1:1.
[0069] Example 4 A method for preparing a dry binder differs from Example 1 in that: The mass ratio of the fiberizable bonding material to the polymerizable monomer is 5:1.
[0070] Example 5 A method for preparing a dry adhesive comprises the following steps: (a) The fiberizable adhesive material was pretreated, comprising ultrasonic treatment, washing, and drying. The ultrasonic treatment frequency was 480 kHz, the ultrasonic treatment time was 5 min, and the ultrasonic treatment temperature was 35°C. The pretreated fiberizable adhesive material was mixed with a polymerizable monomer and an initiator. The fiberizable adhesive material was a tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer; the polymerizable monomer was tetrahydro-2H-2-pyrone, and the mass ratio of the fiberizable adhesive material to the polymerizable monomer was 4:1; the initiator was azobisisobutyronitrile, and the mass ratio of the initiator to the polymerizable monomer was 1:100. The mixing was carried out under nitrogen at a speed of 300 r / min for 10 min to obtain a first system.
[0071] (b) The first system is placed in a constant temperature water bath for heat treatment at a temperature of 55°C for 5 hours. After the reaction is completed, the system is cooled to room temperature. The cooled mixed system is centrifuged and the precipitate is repeatedly washed with a solvent to remove unadsorbed polymer until no polymer is detected in the washing liquid, thereby obtaining a dry binder.
[0072] Example 6 A method for preparing a dry adhesive comprises the following steps: (a) The fiberizable adhesive material is pretreated, comprising ultrasonic treatment, washing, and drying. The ultrasonic treatment frequency is 100 kHz, the ultrasonic treatment time is 20 min, and the ultrasonic treatment temperature is 25°C. The pretreated fiberizable adhesive material is mixed with a polymerizable monomer and an initiator. The fiberizable adhesive material is ethylene-chlorotrifluoroethylene copolymer; the polymerizable monomer is trimesoyl chloride, and the mass ratio of the fiberizable adhesive material to the polymerizable monomer is 4:1; the initiator is azobisisobutyronitrile, and the mass ratio of the initiator to the polymerizable monomer is 1:100. The mixing is carried out under nitrogen at a mixing speed of 50 r / min and a mixing time of 40 min to obtain a first system.
[0073] (b) The first system is placed in a constant temperature water bath for heat treatment at 30°C for 1 hour. After the reaction is completed, the system is cooled to room temperature. The cooled mixed system is centrifuged and the precipitate is repeatedly washed with a solvent to remove unadsorbed polymer until no polymer is detected in the washing liquid, thereby obtaining a dry binder.
[0074] Comparative Example 1 A dry adhesive is provided, using the unpretreated polytetrafluoroethylene in Example 1.
[0075] Comparative Example 2 A dry adhesive, which differs from Example 1 in that: The fiberizable bonding material was not pretreated.
[0076] Experimental example 1. Pole performance test The dry-process binders of each embodiment and comparative example were respectively used to prepare dry-process negative electrode sheets, specifically comprising: stirring and dispersing a mixture of the dry-process binder, the negative electrode active material (graphite) and the conductive agent (conductive carbon black) at low speed (8°C) at a rotation speed of 15m / s; then stirring and fiberizing at high speed (145°C) at a rotation speed of 42m / s to obtain a fiberized electrode material; then placing the electrode material in a Kejing hot roller press for repeated rolling and thinning to obtain a dry-process negative electrode self-supporting film layer with a thickness of 80μm; and hot-pressing and compounding the dry-process negative electrode film layer, the electrode current collector, and the conductive adhesive layer in a hot roller press to obtain a dry-process negative electrode.
[0077] The peeling force test was performed on the dry-process negative electrode sheets obtained in each embodiment and comparative example to evaluate the performance of the modified binder, as follows: 1. Cohesion test method: The obtained dry-process negative electrode sheet was glued to a 50mm×150mm mirror steel plate specially used for peel strength test with 25mm wide double-sided tape, and cut into a 25mm×120mm rectangle. It was fixed on a tensile machine and a 180-degree peel strength test was performed at a tensile speed of 5mm / min.
[0078] 2. Tensile strength test: The tensile strength of the dry-process negative electrode self-supporting film was tested according to the international standard ISO 1184-1983 (Determination of tensile properties of plastic films).
[0079] 2. Battery performance test (1) Preparation of dry cathode Positive electrode formula: LFP:SPPTFE=96.5%:2%:1.5%.
[0080] ① Dry material mixing: Powders such as lithium iron phosphate and conductive agents are mechanically mixed to form a uniform dry powder mixture. ② Fibrillation and mixing of adhesives: The adhesive is processed into a form with a fibrous structure, making it easier to combine with other ingredients during the dry mixing process. ③ Granulation: The fibrillated mixture is made into granules through mechanical granulation equipment. ④ Support film forming, thinning and compaction: The granulated material is passed through a multi-roller device, and the support film is formed after the first rolling. The 2nd-3rd rolling is performed for thinning and compaction (reducing thickness, increasing density, and enhancing electrode performance) to form a layer of stable electrode film with a thickness of 80μm. ⑤ Composite of electrode and current collector: The process of firmly combining the dry electrode film with the current collector. Use hot pressing equipment to combine the electrode film with the current collector.
[0081] (2) Battery preparation Electrode Processing: The dry-process positive and negative electrode sheets prepared in the previous steps are cut to the designed dimensions, ensuring dimensional accuracy and edge quality, and avoiding burrs and dimensional deviations that could affect battery performance. Laser welding is used to weld the tabs to the electrode sheets, ensuring a secure connection and low resistance between the tabs and the sheet. Diaphragm Preparation: The diaphragm material is selected based on the battery design requirements and installed on the diaphragm unwinding mechanism of the stacking machine. Diaphragm tension control and deviation correction are performed to ensure stable tension and correct positioning during the stacking process, preventing wrinkles or shifting that could affect the stability of the battery's internal structure. Lamination: The processed positive electrode sheet is placed on the stacking machine's worktable as the starting layer. The stacking machine's robotic arm applies the diaphragm to the positive electrode sheet according to the specified path and tension, ensuring complete coverage and neat edges. The negative electrode sheet is placed on the diaphragm, aligned with the positive sheet, ensuring accurate relative positioning between the positive and negative electrodes. Repeat the above steps to continue stacking the separator, positive electrode sheets, and negative electrode sheets, following the designed number and sequence of stacking layers to form the basic structure of the battery cell. Battery Cell Shaping: After stacking, the battery cell is shaped to meet the design requirements for its dimensions. This also eliminates any internal stress that may have been generated during the stacking process, improving the stability and consistency of the battery cell. Tab Welding and Leading Out: The tabs of the battery cell are led out and welded to the external connection terminals.
[0082] (3) Battery testing Cycle test: 1C constant current charge to 3.65V, and then constant voltage at 3.65V to 0.05C current cutoff; stand for 20 minutes, then use 1C constant current discharge, cutoff voltage is 2.5V, stand for 20 minutes to complete one cycle.
[0083] DCR test: The battery is charged at a constant current of 1C to 3.65V, then charged at a constant voltage of 3.65V to a current cutoff of 0.05C, left for 1 hour, discharged at a constant current of 1C for 30 minutes, adjusted the SOC to 50%, left for 1 hour, and then discharged at a constant current of 3C for 30 seconds. The DCR value is obtained by the calculation formula.
[0084] The dry-process negative electrode sheets and batteries prepared with the dry-process binders of the embodiments and comparative examples were subjected to performance tests. The test results are shown in Table 1.
[0085] Table 1 Performance test results
[0086] From the above, it can be seen that the dry binder of the present invention sets an elastic polymer layer on the surface of the fiberizable binder material. The dry negative electrode sheet prepared therefrom has excellent negative electrode cohesion and appropriate tensile strength. The obtained battery has a high first efficiency and a high capacity retention rate at high temperature.
[0087] The dry-process negative electrode sheets prepared using the binders in Comparative Examples 1 and 2 have relatively low cohesive force and low tensile strength, and the initial efficiency and high-temperature capacity retention of the resulting batteries are poor.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A dry adhesive, characterized in that: It comprises a base material and an elastic polymer layer arranged on the surface of the base material; The matrix material includes a fiberizable bonding material; The elastic polymer layer is formed by polymerizing monomers, and the polymerizing monomers include at least one of tetrahydro-2H-2-pyrone, trimesoyl chloride, trimethylene carbonate and trifluoropropylene.
2. The dry adhesive according to claim 1, characterized in that Contains the following characteristics (1) or (2): (1) The fiberizable adhesive material includes polytetrafluoroethylene and / or a copolymer containing tetrafluoroethylene; (2) The fiberizable adhesive material includes polytetrafluoroethylene and / or a copolymer containing tetrafluoroethylene; the copolymer containing tetrafluoroethylene includes at least one of ethylene-tetrafluoroethylene copolymer, polyperfluoroethylene propylene, tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer and ethylene-chlorotrifluoroethylene copolymer.
3. The dry adhesive according to claim 1, characterized in that Contains at least one of the following features (1) to (2): (1) The mass of the elastic polymer layer is 2% to 10% of the mass of the dry binder; (2) The thickness of the elastic polymer layer is 2-10 nm.
4. A method for preparing a dry adhesive, characterized in that: The following steps are involved: Mixing a polymerization monomer, an initiator and a pre-treated fiberizable adhesive material to obtain a first system; The first system is subjected to heat treatment and / or ultraviolet irradiation treatment to obtain a dry adhesive.
5. The method for preparing a dry adhesive according to claim 4, wherein: Contains at least one of the following features (1) to (5): (1) The fiberizable adhesive material includes at least one of polytetrafluoroethylene and a copolymer containing tetrafluoroethylene; the copolymer containing tetrafluoroethylene includes at least one of ethylene-tetrafluoroethylene copolymer, polyperfluoroethylene propylene, tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether copolymer, and ethylene-chlorotrifluoroethylene copolymer; (2) The polymerization monomers include one or more of tetrahydro-2H-2-pyrone, trimesoyl chloride, trimethylene carbonate and trifluoropropylene; (3) The mass ratio of the fiberizable adhesive material to the polymerizable monomer is (0.1-10):1; (4) The initiator includes azobisisobutyronitrile; (5) The mass ratio of the initiator to the polymerization monomer is (0.1~5):(80~100).
6. The method for preparing a dry adhesive according to claim 4, wherein: Contains at least one of the following features (1) to (6): (1) The pretreatment includes ultrasonic treatment, washing treatment and drying treatment; the ultrasonic treatment frequency is 100-1000 kHz, the ultrasonic treatment time is 5-20 minutes, and the ultrasonic treatment temperature is 25-50°C; (2) The mixing process is carried out under protective gas conditions; (3) The rotation speed of the mixing process is 50-500 r / min, and the mixing time is 10-40 min; (4) The heat treatment temperature is 30-120°C and the heat treatment time is 1-5 hours; (5) The heat treatment is carried out in a constant temperature water bath and / or a constant temperature oil bath; (6) Cooling and washing the material obtained after the heat treatment to obtain the dry binder.
7. A dry-process negative electrode film, characterized in that: The dry binder is prepared from raw materials including a dry binder, an electrode active material and a conductive agent; the dry binder is the dry binder according to any one of claims 1 to 3 or the dry binder prepared by the preparation method of the dry binder according to any one of claims 4 to 6.
8. The dry-process negative electrode film according to claim 7, characterized in that: Contains at least one of the following features (1) to (2): (1) The dry-process negative electrode film layer includes a dry-process negative electrode film layer; (2) The preparation method of the dry-process negative electrode film layer specifically comprises: subjecting the mixture of the dry-process binder, the electrode active material and the conductive agent to low-temperature mixing treatment, wherein the temperature of the low-temperature mixing treatment is 3-10°C and the linear speed of the dispersion disk of the low-temperature mixing treatment is 5-25 m / s; then subjecting the mixture to high-temperature mixing treatment, wherein the temperature of the high-temperature mixing treatment is 130-150°C and the rotation speed of the high-temperature mixing treatment is 35-45 m / s to obtain an electrode material; and subjecting the electrode material to film-forming treatment to obtain a dry-process negative electrode film layer.
9. A dry-process negative electrode, characterized in that: It comprises an electrode current collector, a conductive adhesive layer and the dry-process negative electrode film layer according to claim 7 or 8; the conductive adhesive layer is located on at least one side surface of the electrode current collector; the dry-process negative electrode film layer is located on the surface of the conductive adhesive layer away from the electrode current collector.
10. A battery, characterized in that: Including the dry-process negative electrode according to claim 9.